Training of Halal Product Process Assistant for Alumni of the UNP Biology Department to Assist Micro and Middle Class Businessman in Self-Declare Halal Certification - Afifatul Achyar; Violita Violita; Rijal Satria; Vauzia Vauzia; Yusni atifah (Fakultas MIPA Universitas Negeri Padang, 2023)
The Halal Product Guarantee Organizing Agency (BPJPH) of the Indonesian Ministry of Religion requires human resources as qualified Halal Product Process Assistants (PPH) to help accelerate the halal certification process for MSE products in Indonesia. On the other hand, there are not many alumni of the Biology Department, FMIPA UNP who got jobs in less than 6 months after graduating. Therefore, the solution offered to the problems faced by partners is to conduct halal product process assistance (PPH) training for alumni of the Biology Department, FMIPA UNP so that they have the capacity and competence to assist MSE business actors in halal certification of their products through a self-declaration scheme. Community service activities consist of two main activities, namely the delivery of material about the halal certification self-declaration scheme and the practice of halal product process assistance (PPH) simulations. The competency of PPH assistants is evaluated and used as an indicator of graduation.